1992
DOI: 10.1680/istbu.1992.18794
|View full text |Cite
|
Sign up to set email alerts
|

Discussion. Model Tests on Masonry Arches.

Abstract: Institute of Higher EducationThe Author's conclusions concur with my own work on 1 m, 1.5 m, 3 m, 5 m, and 6 m span bridge test"-21 which have resulted in the idealization shown in Fig. 17. It is from this theoretical model that the assessing engineer may start and thus determine the relative significance of each component. This allows the different modes of failure to be studied. If the contribution by the spandrel walls to barrel stability is high (which in most cases it will be), transverse distribution bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
2
8
0
1
Order By: Relevance
“…At present, these structures need to be assessed considering current safety requirements and loading conditions. Past laboratory and in-situ tests (Hendry, Davies, & Royles, 1985;Pippard, Tranter, & Chitty, 1936;Pippard & Ashby, 1939;Pippard & Chitty, 1941;Royles & Hendry, 1991;Wang, 2004;Melbourne et al, 2007) showed that the structural response of masonry arches is very complex and characterised by different failure modes. Thanks to the development of computational techniques for nonlinear structural analysis, various numerical strategies for assessing arches in masonry bridges have been proposed in recent past (Nobile & Bartolomeo, 2015;Sarhosis, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, these structures need to be assessed considering current safety requirements and loading conditions. Past laboratory and in-situ tests (Hendry, Davies, & Royles, 1985;Pippard, Tranter, & Chitty, 1936;Pippard & Ashby, 1939;Pippard & Chitty, 1941;Royles & Hendry, 1991;Wang, 2004;Melbourne et al, 2007) showed that the structural response of masonry arches is very complex and characterised by different failure modes. Thanks to the development of computational techniques for nonlinear structural analysis, various numerical strategies for assessing arches in masonry bridges have been proposed in recent past (Nobile & Bartolomeo, 2015;Sarhosis, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While the beneficial effects of the spandrel walls on the ultimate load capacity has been demonstrated (Royles and Hendry, 1991;Melbourne et al, 1997) it has also been recommended that the integrity of the spandrel walls with the arch barrel should not be relied upon for the purposes of ultimate capacity assessment (Page, 1993;.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, over the past few decades a growing interest has developed in studying their behaviour up to collapse and assessing their ultimate load capacity. Significant laboratory and in-situ tests were carried out [3][4][5][6][7][8][9] and different analytical and numerical descriptions were proposed [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Current modelling strategies for arches in masonry bridges are mainly based upon the use of limit analysis concepts [20][21][22], the finite element method (FEM) [13,24,25,26,27], the discrete element method [23] or discontinuous modelling techniques [19].…”
mentioning
confidence: 99%